MANAGING BORNO STATE TERTIARY INSTITUTIONS, CRISES AND THE WAY FORWARD - Bukar, I. B. (Sokoto Educational Review, 2020)
The paper examines the ways tertiary institutions in Borno State are managed. It looks at the sources of fund, crises emanating from managing education tax fund, managing crises resulting from the neglect of college Edicts, and that of interference. The paper also discusses some practical ways for improving management of tertiary institutions in Borno State.